Melanosomal melanin pigment in pleomorphic xanthoastrocytoma, evidence for neuronal‐glial origin: A case report with review of the literature. Issue 2 (19th September 2016) - Gupta, Rakesh K.; Saran, Ravindra K.; Sharma, Mehar C.; Srivastava, Arvind K.; Garg, Lalit
Abstract : We describe a unique case of pleomorphic xanthoastrocytoma (PXA) in a 19‐year‐old male presenting with the chief complaint of seizures. On radiology, the tumor was located in the temporal lobe. It was cortically based and solid cystic in nature. Light microscopy showed pleomorphic large polygonal cells with inclusions, nuclear clustering, lipidization, and foamy cytoplasm intermingled with spindle cells arranged in sweeping pattern and focally containing cytoplasmic brownish black pigment. The pigment stained black with Fontana‑Masson stain and bleached with potassium permanganate. Gomori silver stain showed reticulin fibers surrounding individual tumor cells as well as groups of cells. On immunohistochemistry, tumor cells were positive for GFAP, S‐100 and focally for synaptophysin and CD34 but negative for HMB‐45. CD34 revealed a specific membranous pattern around individual cells as well as groups of cells along the fibers replicating a reticulin pattern. The ultrastructural examination showed supporting melanosomes, thus confirming the melanin pigment. Sequencing for BRAF V600E showed a heterozygous mutation. To our knowledge only five cases of PXA with melanin pigment have been reported and none of which described BRAF V600E mutation analysis. This case provides further insight into the origin and pathogenesis of pigmented astrocytic tumor, additionally highlighting the characteristic CD34 staining pattern.